2019
DOI: 10.1109/tia.2018.2877166
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Degradation Model of Lithium-Ion Batteries for Electric Vehicles

Abstract: The purpose of this paper is to analyse efficiency degradation of lithium-ion batteries. Two lithiumion cell technologies are considered under calendar ageing. It is well known that ageing mechanisms have an impact in cells' performances. Most of studies focus on capacity fade and impedance rise but efficiency is less frequently studied. However, from the application point of view, battery efficiency degradation directly impacts the system energy efficiency. Results reveal the importance of considering battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Power is likewise reduced when parasitic reactions occur that convert battery materials to other compounds that act as transport barriers, increasing the cell's internal impedance, and which in turn reduces the operating voltage at each discharge rate [88,89]. A recent report highlights the high correlation between capacity fade and energy efficiency of the cell (i.e., low hysteresis), presumably due to the low impedance of the solid electrolyte interphase of the new cell, and the rate at which this interphase therefore changes [90,91]. This section reviews some of the key issues that can affect the overall State of Health (SOH) of those batteries, e.g., the ability to deliver power compared to a new pack, and provides a review of several current research areas that help address the issues.…”
Section: Li-ion Battery Lifespanmentioning
confidence: 99%
“…Power is likewise reduced when parasitic reactions occur that convert battery materials to other compounds that act as transport barriers, increasing the cell's internal impedance, and which in turn reduces the operating voltage at each discharge rate [88,89]. A recent report highlights the high correlation between capacity fade and energy efficiency of the cell (i.e., low hysteresis), presumably due to the low impedance of the solid electrolyte interphase of the new cell, and the rate at which this interphase therefore changes [90,91]. This section reviews some of the key issues that can affect the overall State of Health (SOH) of those batteries, e.g., the ability to deliver power compared to a new pack, and provides a review of several current research areas that help address the issues.…”
Section: Li-ion Battery Lifespanmentioning
confidence: 99%
“…For the purpose of this work, we are not considering SoC drift influence in the identification process. In fact, a sensible SoC drift influence was found in LFP/C cells [23] but not in NMC/C cells which are studied here [24]. Another important assumption is to consider that C a is independent of the State of Health (SoH), meaning that at each SoC level a value of C a can be found independently of the current capacity loss.…”
Section: Parameter Identificationmentioning
confidence: 82%
“…A parameter identification is performed to fit our model (C a ) to the results of calendar ageing tests ( Figure 2). This task has already been reported in References [23,24]. For the purpose of this work, we are not considering SoC drift influence in the identification process.…”
Section: Parameter Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the degradation in the efficiencies is very small. In a case study [33], it is shown that the efficiency of the li-ion battery degrades from 95% to 94% over the lifetime. Another study [34] also shows similar results.…”
Section: B Motivationmentioning
confidence: 99%